Analysis on Fast Breeder Reactor (FBR) Performances and Plutonium Production Profile of Loading Minor Actinide (MA) in FBR Blanket - Sidik Permana; Mitsutoshi Suzuki; Masaki Saito (Institut Teknologi Bandung, 2012)
An investigated process of recycling option based on minor actinide (MA) composition in the reactor design has been investigated which is based on fast breeder reactor (FBR) type as reference reactor type. The paper investigated some significant parameters of reactor operation, fuel sustainability and nuclear non-proliferation point of view. As initial fuel composition some composition of light water reactor (LWR) spent fuels are used and loaded into the such as mixed oxide (MOX) in the core regions and minor actinide doping is loaded into blanket regions. It is shows that criticality condition as indicating reactor operation time is obtained less for loading MA case in the blanket regions in comparing with no loading MA. It indicates a shorter reactor operation time is obtained for loading MA than without loading MA. Conversion rasio level or breeding rasio, is obtained less conversion rasio for loading MA which shows less fissile material production when some portion of U-238 is replaced by MA loading. Although, during reactor operation, some fissile plutonium materials such as Pu-239 are also produced from MA loading, however, it still less production in comparing with fissile plutonium production from direct process from converted U-238. It shows more Pu-238 can be produced than Pu-240 because of main portion of MA is Np-237 which can be directly produce more Pu-238 than Pu- 240. As protected plutonium composition (Pu-238 and Pu-240), loading MA produces some even mass plutonium isotopes in the blanket regions and loading 5 % of MA doping, obtains more than enough composition based on Kessler’criterion to estimate the level of technical difficulty for contructing explosive nuclear devices based on internal heating of Pu-238.